Perancangan Etalase Toko Fashion dengan Sistem Modular - Setiadi, Jovita Kolin; Kusumarini, Yusita; Suryanata, Linggajaya (Intra, 2015)
Nowadays lifestyle rapidly increases especially in the fashion industry. This makes many entrepreneurs start their business in retail fashion industry. The high competition demands entrepreneurs should have strategies in order to attract consumers' interest, one of the ways is by redesigning their window display areas. Therefore, a system is needed to be applied in window display area design with the emphasis on practicality in assembling. To achive this, the design requires observation, literature study and trials. As the base of the working process, this design applies the David Kelley’s design thinking method which done through numerous phases such as empathise phase (early phase), define (determining phase), ideate (ideation phase), prototype (trial and error) and test (the application).This design has 4 choice of categorized sets which are bag’s category, footwear’s category, clothing’s category and mix category. The applied system of this product is a modular system that has ease of assemble for the users. This design has the advantages which are the various different forms that can be created from modules in each category, as well as the budget cost which is affordable for fashion store entrepreneurs.